DPPC-coated lipid nanoparticles as an inhalable carrier for accumulation of resveratrol in the pulmonary vasculature, a new strategy for pulmonary arterial hypertension treatment - Zerong Li; Wenmei Qiao; Chenghao Wang; Heqiao Wang; Mengchao Ma; Xinyu Han; Jingling Tang (Taylor & Francis Group, 2020)
In this study, we investigated the feasibility of dipalmitoylphosphatidylcholine-coated lipid nanoparticles (DPPC-LNs) as a carrier for preferential accumulation into lungs of Resveratrol (Res), a potentially promising drug for the treatment of pulmonary arterial hypertension (PAH). Res-loaded DPPC-LNs were prepared following a thin film hydration-ultrasonic dispersion technique using glyceryl monostearate as lipid core. DPPC can reduce the interactions between nanoparticles and pulmonary surfactant. The optimal formulation was prepared and characterized for physicochemical properties, storage stability and in vitro release profiles. The optimal formulation was evaluated for uptake by pulmonary arterial smooth muscle cells (PASMCs) using fluorescence microscopy. The efficacy of Res-loaded DPPC-LNs in reducing hyperplasia was tested in 5-HT induced proliferated PASMCs. The drug absorption profiles upon intratracheal administration were monitored in healthy rats. Optimized spherical DPPC-LNs - with mean size of 123.7 nm, zeta potential of -19.4 mV and entrapment efficiency of 94.40% - exhibited an 80% cumulative drug release over 48 h. Fluorescence microscopic study revealed an time-dependent enhancement of cellular uptake of Rh123-labeled DPPC-LNs by PASMCs. PASMC proliferation induced by 5-HT was significantly inhibited by Res-loaded DPPC-LNs. Optimized DPPC-LNs appeared to be safe when incubated with PASMCs. Besides, plasma and lung tissue data analysis indicated higher value of accumulation after intratracheal administration of Res-loaded DPPC-LNs in comparison with the intravenously dosed Res solution, indicating longer retention of Res in the lungs and their slower entry to the systemic blood circulation. DPPC-LNs could be a viable delivery system for site-specific treatment of PAH.